The Maternal Fetal Triage Index: A Standardized Approach to OB Triage. Issue 6 (November 2016) - Killion, Molly M.
Abstract : The Association of Women's Health, Obstetric, and Neonatal Nurses has developed and validated the Maternal Fetal Triage Index. This standardized approach to assessing and assigning acuity of pregnant women who present to the hospital for care may be an effective and safe way to allocate care and resources. The American College of Obstetricians and Gynecologists also is recommending use of this type of tool.